`There`s nothing you can do`: multi-level factors affecting the careers of female football coaches in Poland - Organista, N.; Kossakowski, R. (Sport in Society: Cultures, Commerce, Media, Politics, 2025)
The main objective of this article is to examine the professional experiences of female football coaches in Poland. Existing research within the field of coaching science has highlighted a noticeable underrepresentation of women in this profession. However, the available data on this topic is limited to specific areas. By utilizing Brofenbrenner`s ecological systems theory, this study aimed to identify the primary obstacles female coaches encounter and the few factors that support women in this coaching realm. The findings of this study could potentially contribute to a more inclusive and diverse coaching landscape in Poland and beyond. Drawing from qualitative interviews (n = 7), the results illuminate a multifaceted array of challenges the participants face at different stages of their careers, varying in intensity. The findings underscore the remarkable resilience of Polish female coaches, who confront barriers predominantly emanating from socio-cultural presumptions prevailing within the football community. These challenges are compounded by perceptions of the game as inherently `masculine` and Polish society`s conventional constructs of masculinity and femininity.